DYNAMIC ANALYSIS OF JACKET TYPE OFFSHORE STRUCTURE UNDER IMPACT OF WAVE AND WIND USING STOKE’S SECOND ORDER WAVE THEORY - Chung, Nguyen Thai; Anh, Le Hoang (Vietnam Journal of Marine Science and Technology, 2015)
This paper presents finite element algorithms and dynamic analysis of the jacket type offshore structure under water wave and wind impact by using stoke’s second order wave theory. The result of the paper is the scientific basis for the calculation, design and selection of the appropriate parameters, the study contributes to the optimization of fixed offshore structures such as buildings DKI, serving defense, security and contributing to improving the capacity to defend Vietnam’s sovereignty over seas and islands.